Cooperative magnetic interactions in three mononuclear copper Schiff base complexes - Guskos, N.; Typek, J.; V. Likodimos; Glenis, S.; Dziembowska, T.; Wabia, M.; Palios, G.; Lin, C.L. (Materials Chemistry and Physics, 2004)
The magnetic properties of three mononuclear copper complexes where the metal ion is coordinated by Schiff base ligands have been investigated by magnetic susceptibility and electron paramagnetic resonance (EPR) studies. Significant extended magnetic coupling has been observed comprising competing antiferromagnetic and ferromagnetic components, which are explained in terms of the interactions between copper ions mediated through the organic ligands. Distant substitutions in the ligand structure are suggested to affect critically the magnetic coupling leading to frustration effects on the cooperative transition that may develop under favorable structural conditions. The temperature dependence of intensity of the EPR line was studied in the temperature range 130-280K and fitted to the Curie-Weiss-type law. The consistency of magnetic and EPR results is discussed for the three investigated complexes. © 2003 Elsevier B.V. All rights reserved.
cited By 2